2017
DOI: 10.1177/1078345817727730
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Inmates Who Misuse Prescription Medication

Abstract: Substance use disorders are common among incarcerated individuals, and prescribed medications have been reported as abused, diverted, or otherwise misused in correctional settings. We conducted a retrospective chart review of electronic medical records and reports on institutional charges for misuse of authorized medication by inmates in the New Jersey Department of Corrections between 2003 and 2013. The most frequently cited medications for misuse were gabapentin, diphenhydramine, clonidine, and ibuprofen. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Trihexyphenidyl (Tamburello et al, 2017). Quetiapine is currently neither a controlled medicine nor categorized as a narcotic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Trihexyphenidyl (Tamburello et al, 2017). Quetiapine is currently neither a controlled medicine nor categorized as a narcotic.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with Cunningham (2006), it was suggested that inmates with a history of being on medication for psychiatric disorders often abuse those medicines, which also may be traded in prison. The medicines that are found and commonly used in prisons are Quetiapine, Olanzapine, Gabapentin, Bupropion, and Trihexyphenidyl (Tamburello et al., 2017). Quetiapine is currently neither a controlled medicine nor categorized as a narcotic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The misuse of prescription medications apart from OST medications, such as tranquilizers, antidepressants (mirtazapine), benzodiazepines, antipsychotics (quetiapine, olanzapine), anticonvulsants (pregabalin, gabapentin), and even paracetamol (acetaminophen), has also been reported to be an increasing problem in many prisons, particularly for women (Bi‐Mohammed et al, 2017; Duke & Trebilcock, 2022; Hampton et al, 2015; May et al, 2019; O'Hagan & Hardwick, 2017; Penfold et al, 2005; Rousselet et al, 2019; Sahajian et al, 2017; Tamburello et al, 2017; Zurhold et al, 2005). Women have been found to be more likely to misuse prescription medications than men in both prisons and the community (UNODC, 2021).…”
Section: Types Of Drugs Used In Prisonmentioning
confidence: 99%
“…After 2013, the reported use of heroin in prison declined, while the use of buprenorphine, which is a common opioid substitution treatment (OST), increased. Other prisons around the world have found an increase in the misuse of OSTs, particularly buprenorphine, as well, likely due to them being less expensive than heroin; being more easily obtainable than heroin due to the possibility for the diversion of prescription OST medications and availability of formulations that can be more easily smuggled, such as sublingual films and tablets; often requiring smaller quantities; and the widespread belief among prisoners that buprenorphine is not able to be detected in urine drug screens (Bi‐Mohammed et al, 2017; Mjåland, 2014, 2016; Mohammed et al, 2016; Monico et al, 2021; Mravčík et al, 2018; Penfold et al, 2005; Plugge et al, 2009; Rousselet et al, 2019; Tamburello et al, 2017; Tompkins, 2016; Tompkins et al, 2009; White et al, 2016; Wright et al, 2014).…”
Section: Types Of Drugs Used In Prisonmentioning
confidence: 99%